2002
DOI: 10.1111/1467-7679.00173
|View full text |Cite
|
Sign up to set email alerts
|

Policy Lessons for Prudential Regulation in Developing Countries

Abstract: This article draws together the regulatory policy lessons arising from the Finance and Development Research Programme's project on prudential regulation and supervision of the financial sector in low-income countries. The policy recommendations include: bringing regulations, such as loan provisioning rules, into line with international standards, where this has not already been done; tightening bank licensing procedures and raising minimum capital requirements; introducing 'prompt corrective action rules'; pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The main objective of prudential regulation is to safeguard the stability of the financial system and to protect deposits. However, the prudential reforms already implemented in developing countries have not been effective in preventing banking crises, and a question remains as to how pru-dential systems can be strengthened to make them more effective (Brownbridge, 2002).…”
Section: Deregulation Of Banks In Developing Economiesmentioning
confidence: 99%
“…The main objective of prudential regulation is to safeguard the stability of the financial system and to protect deposits. However, the prudential reforms already implemented in developing countries have not been effective in preventing banking crises, and a question remains as to how pru-dential systems can be strengthened to make them more effective (Brownbridge, 2002).…”
Section: Deregulation Of Banks In Developing Economiesmentioning
confidence: 99%
“…This study showed that US banks displaying risk of insolvency escaped PCA as they are not considered undercapitalized based on the existing risk-based capital. Brownbridge (2002) studied policy lessons for prudential regulation in developing countries. The study recommended, including prompt corrective action rules, providing regulators with an unambiguous mandate to protect deposits and the financial system's stability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research interests around PCA have their origin in 1991 with the implementation of the Federal Deposit Insurance Corporation (FDIC) Improvement Act (FDICIA). Studies revolved around bank recovery efforts (Dahl and Spivey 1995;Garcia 1995), revised solvency measures (Jones and King 1995), depositor protection, insurance (Brownbridge 2002;Sumathy and Venkatachalam 2019;Schich 2008;Gulati 2020), and regulator forbearance, effectiveness (Garcia 2010;Kagade 2015). Extant research also suggests modifications in the PCA framework through continuous improvement in the regulatory capital ratios (Jones and King 1995), inclusion of new tailored triggers, alternative, and additional triggers (Svoronos 2018;Cole and White 2017;Council, Financial Stability Oversight 2011), and revamping prudential regulation (Loveland 2016).…”
Section: Introductionmentioning
confidence: 99%